Using game-based learning in developing metacognition among ESP students: a case study / Tan Wilson, Nadya Supian and Cheah Kok Sung - Tan, Wilson; Supian, Nadya; Cheah, Kok Sung (Universiti Teknologi MARA, 2023)
Undergraduates in higher education institutions in developing countries are often required to enroll in courses like English for Specific Purposes, to enhance their English language proficiency in different disciplines. Other than language learning, these courses are also designed to develop cognitive skills. One of these is metacognition, which concerns an individual’s cognitive capabilities to plan, execute, monitor and evaluate tasks, and that needs to be developed and strengthened at tertiary levels of education prior to embarking on a career. To that end, a digital simulation game was introduced as supplementary material for an ESP (Business English) class during a semester, with the aim of facilitating and developing metacognitive awareness and strategy use as well as foster incidental language learning. This qualitative case-study explores the learners’ experiences with using the digital simulation video game The Sims 4: Get to Work (Retail) to support their learning of Business English and develop their metacognition. Findings revealed that learners displayed declarative knowledge, procedural knowledge, and conditional knowledge of metacognitive processes during the game play, and indicated ability to regulate their cognitive processes to achieve the business goals of the retail simulation game, while using Business English. Implications of these findings suggest that the implementation of simulation game-based learning is highly beneficial for students, enabling them to develop both their metacognitive skills and communication within ESP contexts.